Fast Protein Modification in the Nanomolar Concentration Range Using an Oxalyl Amide as Latent Thioester. Issue 29 (31st May 2022) - Snella, Benoît; Grain, Benjamin; Vicogne, Jérôme; Capet, Frédéric; Wiltschi, Birgit; Melnyk, Oleg; Agouridas, Vangelis
Abstract: We show that latent oxalyl thioester surrogates are a powerful means to modify peptides and proteins in highly dilute conditions in purified aqueous media or in mixtures as complex as cell lysates. Designed to be shelf‐stable reagents, they can be activated on demand to enable ligation reactions with peptide concentrations as low as a few hundred nM at rates approaching 30 M −1 s −1 . Abstract : Oxalyl thioesters are cell metabolites endowed with remarkably powerful acyl transfer abilities. The bioinspired design of stable and activatable oxalyl thioester surrogates and their application for the modification of peptides and proteins is reported. Formation of a stable oxalamide crosslink proceeds at rates ≈30 M −1 s −1, in the nanomolar concentration range, in purified media or in protein extracts of cell lysates.